KETELADANAN DAKWAH DI TENGAH MASYARAKAT MULTIKULTURAL - Rafdeadi Rafdeadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2013)
This paper aims to give an alternative perspective for successing religious preaching. Of the religious preaching’s intention is to create the religious community. The activities of religious preaching have been doing since prophet’s era until now with different methods and approaches. The condition depend on the faced social and cultural context of society. There are many methods which can be done in religius preaching, starting from verbal, text and context become good model. The most common verbal form of religious preaching is frequently used by religious preacher in delivering their Islamic messages. But in the contex of modernity, this pattern must be rethinking about its effectiveness in gaining the goal of religius preaching. Morever in the context of globalization, it need a new approaches in delivering Islamic messages, not only verbal context but also contextual one. One of contextual form is examplary dakwah in the community. Becouse the similarity between statement and activity, good personality, honest, naturality, and attension can be one of the successful of Islamic dakwah. That’s why, the next model of Islamic dakwah must include the examplary dakwah become alternative strategy for Islamic dakwah especially in the multicultural people.